Fluency Matters! Chinese Netizens’ Attitudes towards China English - Qi Sun; Ying Qi Wu (UIN Salatiga, 2022)
This research examined Chinese netizens’ attitudes towards China English (CE), a growing English variety in China, as well as the underlying reasons for their attitudinal responses. The corpus consisted of 905 tokens of Danmus (a form of video synchronous commentary used by netizens on the Internet video) that were collected from an online interview video. Instead of adopting the frequently employed questionnaire survey, these unique Danmus were utilized as the data resource and were analyzed via a paradigmatic approach to investigate Chinese netizens’ acceptance of some potential features of CE. Four netizens were invited to an interview to investigate the reasons for their Danmu delivery on language attitudes. The results revealed that Chinese netizens showed overwhelmingly positive attitudes towards CE, which differed significantly from earlier findings. The participants' positive evaluations of CE were based on three key parameters: the fluency and confidence in using CE as a communicative tool, the possibility of CE to mark speakers' Chinese identity, and the ease of using CE in communication. The findings of the study may shed light on the increasing awareness of China English and English globalization among Chinese netizens in the web-mediated context where local varieties of English are emerging. This research also hopes to provide some methodological implications in terms of research subjects and data-collection approaches for current investigations of language attitudes. This study offers some pedagogical implications of introducing English varieties, especially China English, to the English language programs in China.Keywords: China English, Danmus, Chinese netizens, language attitudes, English language teaching